Evidence that a STAT3 Mutation Causing Hyper IgE Syndrome Leads to Repression of Transcriptional Activity. (13th October 2019) - Bahal, Sameer; Houssen, Maha E.; Manson, Ania; Lorenzo, Lorena; Russell, Mark A.; Morgan, Noel G.; Tahami, Fariba; Grigoriadou, Sofia
Abstract : We present the case of a 19-year-old female with a mild form of Autosomal Dominant Hyper IgE syndrome (HIES) associated with a loss-of-function mutation in STAT3 . Within the first years of life she developed multiple, Staphylococcus aureus associated abscesses in the neck and face requiring frequent incision and drainage. Respiratory tract infections were not a feature of the clinical phenotype and a high resolution thoracic CT scan was unremarkable. Retained dentition was noted but fungal nail disease and recurrent thrush were absent. The total IgE was 970 IU/L, Lymphocyte counts and immunoglobulin levels were normal (IgG borderline 18.5 gr/L). There was suboptimal response to test immunisation with Pneumovax II vaccine. Th17 cell phenotyping revealed low levels of IL-17 expressing cells (0.3% of total CD4 T Cells numbers). Genetic analysis identified a missense mutation, N567D, in a conserved region of the linker domain of STAT3. Functional studies in HEK293 cells reveal that this mutation potently inhibits STAT3 activity when compared to the wildtype protein. This is consistent with other reported mutations in STAT3 associated with HIES. However, surprisingly, the magnitude of inhibition was similar to another STAT3 mutation (V637M) which causes a much more severe form of the disease.